KONSTRUKSI IDENTITAS KULTURAL “WONG NGAPAK” MELALUI KONSUMSI MEDIA DIALEK BANYUMASAN - Siti Khusnul Khotimah (Studi Budaya Nusantara, 2017)
This thesis entitled "The Construction of Cultural Identity of Wong Ngapak through the consumption of local media in Banyumasan dialect" which studied the use of radio Programme "Curanmor" by three students from Cilacap in Yogyakarta and the positioning of their cultural identity through central and periphery perspective. The study applied ethnographic research methods in the context of data collection and to explain the patterns and cultural practices of the student from Cilacap in consuming media. In order to analyse the data, author implemented theory of Media Consumption, Cultural Identity and Central – Periphery Perspective. The approach used in this audience study is based on the model of audience-as-agent which considers the audience as an active agent. Audiences consumed media "Curanmor" to construct their cultural identity in Yogyakarta by (1) "Curanmmor” as a cultural symbol for Banyumasan community; (2)" Curanmor” is used as a 'going back home’ experience, (3) "Curanmor" as the media to strenghten Banyumasan Culture dan dialect, (4) Curanmor "as a 'cultural distinctiveness' ; (5)" Curanmor "as soft-resistance of the marginalization of Banyumasan culture. The five ways of the use of these media are forms of the construction of cultural identity that may erode the negative images and stereotypes of the Banyumasan language and culture in the region of Yogyakarta as a result of the unequal binary perspective, central and periphery. Yogyakarta and its culture is considered as central ( "the Self"), while the culture and Ngapak language regarded as "the Other". By constructing and reconstructing cultural identity, it is expected that the culture and Ngapak language are no longer marginalised in the context of Javanese culture itself. Each culture may raise without any domination of one culture to others.